Impact of (intestinal) LAL deficiency on lipid metabolism and macrophage infiltration - Valentina Bianco; Melanie Korbelius; Nemanja Vujic; Alena Akhmetshina; Melina Amor; Dagmar Kolb; Anita Pirchheim; Ivan Bradic; Katharina B. Kuentzel; Martin Buerger; Silvia Schauer; Huyen T.T. Phan; et al. (Elsevier, 2023)
Objective: To date, the only enzyme known to be responsible for the hydrolysis of cholesteryl esters and triacylglycerols in the lysosome at acidic pH is lysosomal acid lipase (LAL). Lipid malabsorption in the small intestine (SI), accompanied by macrophage infiltration, is one of the most common pathological features of LAL deficiency. However, the exact role of LAL in intestinal lipid metabolism is still unknown. Methods: We collected three parts of the SI (duodenum, jejunum, ileum) from mice with a global (LAL KO) or intestine-specific deletion of LAL (iLAL KO) and corresponding controls. Results: We observed infiltration of lipid-associated macrophages into the lamina propria, where neutral lipids accumulate massively in the SI of LAL KO mice. In addition, LAL KO mice absorb less dietary lipids but have accelerated basolateral lipid uptake, secrete fewer chylomicrons, and have increased fecal lipid loss. Inflammatory markers and genes involved in lipid metabolism were overexpressed in the duodenum of old but not in younger LAL KO mice. Despite the significant reduction of LAL activity in enterocytes of enterocyte-specific (iLAL) KO mice, villous morphology, intestinal lipid concentrations, expression of lipid transporters and inflammatory genes, as well as lipoprotein secretion were comparable to control mice. Conclusions: We conclude that loss of LAL only in enterocytes is insufficient to cause lipid deposition in the SI, suggesting that infiltrating macrophages are the key players in this process.